2008
DOI: 10.1063/1.2991299
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sb and As segregation at the InP on GaAsSb interface

Abstract: We study the formation of the InP on GaAsSb interface grown by molecular beam epitaxy at 450 °C. Using angle resolved x-ray photoemission spectroscopy (XPS), we show that Sb strongly segregates whereas As does not, leading to a Sb-rich InP surface. Similarly, XPS spectra recorded on air-exposed samples reveal oxidized Sb but no oxidized As. We perform a quantitative analysis and determine a Sb segregation coefficient very near to 1. This result is in good agreement with previous reflectance anisotropy spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This suggests that Sb diffuses to the surface during As-decapping procedure which is most likely due to the binding energy difference between GaAs and GaSb binary systems. 27 In the case of GaAsSb, GaAs binary system has higher binding energy than GaSb, which results in a lower kinetic barrier to Sb segregation. 28 Since we showed that the Sb capping layer produces a chemically clean starting surface compared to As capping, we use this to investigate the interfacial chemistry of Al 2 O 3 ALD directly on the Sb-decapped surface.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Sb diffuses to the surface during As-decapping procedure which is most likely due to the binding energy difference between GaAs and GaSb binary systems. 27 In the case of GaAsSb, GaAs binary system has higher binding energy than GaSb, which results in a lower kinetic barrier to Sb segregation. 28 Since we showed that the Sb capping layer produces a chemically clean starting surface compared to As capping, we use this to investigate the interfacial chemistry of Al 2 O 3 ALD directly on the Sb-decapped surface.…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced by EDX data some intermixing occurs in the InAs top layer. Sb segregation is a well-known phenomenon [42], probably enhanced in our growth conditions using a relatively low growth rate. Ga segregation/ interdiffusion in InAs is less expected and further work is needed to clarify this point.…”
Section: Nanostructure Strain Relaxationmentioning
confidence: 87%
“…One is the slight incorporation of Sb in the InP emitter. This is probably due to Sb (surface) segregation [24][25][26][27] and memory effects. An appropriate growth interval process in an As-rich atmosphere before the growth of InP 24,25) and=or the insertion of a GaAs interlayer 28) between the base and the InP emitter might be effective for suppressing this segregation.…”
Section: Sims Analysis and Contact Resistivity Of Compositionally-gra...mentioning
confidence: 99%